Pusat Seni Karikatur Di Pekanbaru Dengan Prinsip Perancangan Frank Owen Gehry - Yoshua Gilbert Winalda; Mira Dharma Susilawaty; Yohannes Firzal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Carricature artist in Pekanbaru is need a place for them to improve their skill of showing expression in art by their carricarture painting art. Carricature art center is the solution for carricature artist whose need a place to learn, create and to express imganination in art and could be a symbol of identity for carricarture artist. Design principle of Frank Owen Gehry architect will aply to carricature art center design to rise up the symbol and a movement of art to be a big idea and transform it to be a iconic building. A big concept of designing carricature art center is “The Peoples Againts The Mighty Goverment”. The concept strategy is to representatate an expression of carricature artist whose create a critical communication by painting art. Same with gehry architect the strategy of designing Carricature art center begin from tranformation of abstractionthe symbol of “The peoples Againts The Mighty Goverment”to be a form of building. Finally, based on Frank Owen Gehry principle design strategy and the concept the final results of carricature art center design are abstract form of building,flexible and non-geomtry building form, and contrass material and color building.Key words: Carricature Art Center, Expression, Principle, Frank Owen Gehry